A hybrid switched inductor with flexible high voltage gain boost converter for DC micro‐grid application - Mohammed Al‐Hitmi (20399063) (2021)
A hybrid switched inductor with flexible high voltage gain boost converter for 400 V DC microgrid application is presented in the paper. The three operating modes of the converter are controlled using three switches by two-duty ratios. The proposed converter provides flexibility in the selection of the duty cycle to achieve desired output voltage. Moreover, with two duty ratio, high gain with a wide duty range is accomplished in the proposed converter while an individual switch does not need to operate at a very large duty ratio. The power circuit analysis, operating principles, steady-state voltage gain analysis during continuous conduction mode (CCM) and discontinuous continuous mode (DCM), boundary condition, efficiency analysis, comparison, and circuit parameter design of the proposed are presented. A closed-loop controller design and small-signal modeling are discussed. The dynamic behavior of the proposed converter is validated with a change in duty ratio, input voltage, and load power. A laboratory prototype converter is designed and developed to verify the model, and feasibility of different operation modes. The prototype is tested for a power range of 100 W–500 W for different duty cycles. Other Information Published in: IET Power Electronics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/pel2.12140